Enhancing Students’ Speaking Skill through A Communicative Approach with The Simon Says Game - Hermansyah; Adijaya, Nuryansyah; Hadianti, Siti (English Study Program, Faculty of Teacher Training and Educational Sciences, Universitas Timor, 2024)
Effective communication is essential in learning English, especially in the speaking aspect. This challenge was evident at SMPN 22 West Jakarta, where students struggled to communicate with their teachers due to language barriers. To address this, the researcher conducted a study in class 9F, involving 33 students, using Classroom Action Research (CAR) across three cycles. The class was chosen due to limited interaction and communication during English lessons. The goal was to improve students' speaking skills through a communicative approach, supplemented with the Simon Says game. The results showed significant improvement in speaking skills. In cycle I, only 11 out of 33 students (33%) could speak English. By cycle III, this number increased to 100%, demonstrating that the communicative approach combined with the Simon Says game was effective in enhancing speaking skills at the junior high school level.